2016
DOI: 10.3390/app6010025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Theoretical and Machine Learning Methods for Acquiring Compressed Liquid Densities of 1,1,1,2,3,3,3-Heptafluoropropane (R227ea) via Song and Mason Equation, Support Vector Machine, and Artificial Neural Networks

Abstract: 1,1,1,2,3,3,3-Heptafluoropropane (R227ea) is a good refrigerant that reduces greenhouse effects and ozone depletion. In practical applications, we usually have to know the compressed liquid densities at different temperatures and pressures. However, the measurement requires a series of complex apparatus and operations, wasting too much manpower and resources. To solve these problems, here, Song and Mason equation, support vector machine (SVM), and artificial neural networks (ANNs) were used to develop theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…After output data is compared with the other results, the iteration process is finished and the closest estimate is obtained. There are various studies focusing on ANN at theoretically, such as Shojaeefard et al [22], Li et al [23]. A diagram of a multilayer feed forward neural network model structure used in this study is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After output data is compared with the other results, the iteration process is finished and the closest estimate is obtained. There are various studies focusing on ANN at theoretically, such as Shojaeefard et al [22], Li et al [23]. A diagram of a multilayer feed forward neural network model structure used in this study is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…SVM is a powerful machine learning method based on the statistical learning theory [20][21][22]. With limited information of samples between the complexity and learning ability of models, this The lengths of the tested samples referred to the standards of both China and Japan [11][12][13], which were 230 mm.…”
Section: Svmmentioning
confidence: 99%
“…This plane not only helps improve the predictive ability of the model, but also helps reduce the error which occurs occasionally when classifying. Figure 3 is the main structure of a typical SVM [16,22]. The letter "K" represents kernels.…”
Section: Svmmentioning
confidence: 99%
See 2 more Smart Citations